THE FOSTERING OF CORRUPTION INMATES IN SUKAMISKIN CLASS I CORRECTIONAL FACILITY - Kusmiyanti Kusmiyanti (Asia Pacific Fraud Journal, 2018)
The purpose of this research is to observe the implementation of the fostering of corruption inmates in Sukamiskin Correctional Facility. This research uses a qualitative approach. The results of this research show that the implementation of fostering in Sukamiskin Class I Correctional Facility has not been in accordance with the concept of Correctional. The fostering of the corruption inmates is focused on the personality only. The strengthening of religious values is conducted by ustadz, pastor, and other religious leaders. The development of independence has not in line with the concept of correctional. Therefore, in addition to having expertise, correctional officers must also have a high sense of devotion. Correctional officers must uphold the concept of correctional firmly based on the principles of Pancasila and continue to view inmates as God’s creatures, as individuals and as members of society.